2021
DOI: 10.1002/etc.5041
|View full text |Cite
|
Sign up to set email alerts
|

Methylmercury Production and Degradation under Light and Dark Conditions in the Water Column of the Hells Canyon Reservoirs, USA

Abstract: Methylmercury (MeHg) is a highly toxic form of mercury that can bioaccumulate in fish tissue. Methylmercury is produced by anaerobic bacteria, many of which are also capable of MeHg degradation. In addition, demethylation in surface waters can occur via abiotic sunlight-mediated processes. The goal of the present study was to understand the relative importance of microbial Hg methylation/demethylation and abiotic photodemethylation that govern the mass of MeHg within an aquatic system. The study location was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…MeHg can be degraded either directly or indirectly by light through photolysis or photochemical reactions, a mechanism so-called photodemethylation (Figure ). Photodemethylation is obviously only significant in surface water due to rapid attenuation of light in the water column, especially for ultraviolet (UV) radiation. ,, Additionally, the rate and efficiency of photodemethylation strongly depend on the radiation intensity and wavelength; shorter waveband UV-B light (280–320 nm) is far more effective in degrading MeHg than longer waveband UV-A light (320–400 nm) and the visible or photosynthetic active radiation (PAR) (400–700 nm). ,,, For example, in a study of photodemethylation along a lake-wetland gradient in a boreal coniferous forest, the relative ratio of demethylation rate constants with UV-B, UV-A, and PAR was found to be 3100:43:1 in surface waters . Similarly, Black et al reported that photodemethylation rate constants were at least 400-fold greater for UV-B and 37-fold greater for UV-A than PAR in water.…”
Section: Abiotic Demethylationmentioning
confidence: 99%
See 1 more Smart Citation
“…MeHg can be degraded either directly or indirectly by light through photolysis or photochemical reactions, a mechanism so-called photodemethylation (Figure ). Photodemethylation is obviously only significant in surface water due to rapid attenuation of light in the water column, especially for ultraviolet (UV) radiation. ,, Additionally, the rate and efficiency of photodemethylation strongly depend on the radiation intensity and wavelength; shorter waveband UV-B light (280–320 nm) is far more effective in degrading MeHg than longer waveband UV-A light (320–400 nm) and the visible or photosynthetic active radiation (PAR) (400–700 nm). ,,, For example, in a study of photodemethylation along a lake-wetland gradient in a boreal coniferous forest, the relative ratio of demethylation rate constants with UV-B, UV-A, and PAR was found to be 3100:43:1 in surface waters . Similarly, Black et al reported that photodemethylation rate constants were at least 400-fold greater for UV-B and 37-fold greater for UV-A than PAR in water.…”
Section: Abiotic Demethylationmentioning
confidence: 99%
“…Photodemethylation is obviously only significant in surface water due to rapid attenuation of light in the water column, especially for ultraviolet (UV) radiation. 159 , 160 , 165 Additionally, the rate and efficiency of photodemethylation strongly depend on the radiation intensity and wavelength; shorter waveband UV-B light (280–320 nm) is far more effective in degrading MeHg than longer waveband UV-A light (320–400 nm) and the visible or photosynthetic active radiation (PAR) (400–700 nm). 33 , 160 , 161 , 166 170 For example, in a study of photodemethylation along a lake-wetland gradient in a boreal coniferous forest, the relative ratio of demethylation rate constants with UV-B, UV-A, and PAR was found to be 3100:43:1 in surface waters.…”
Section: Abiotic Demethylationmentioning
confidence: 99%
“…MeHg accumulated in these strata, in both filter-passing and particulate fractions, and increased longitudinally both up and downgradient in Brownlee Reservoir with the spread of anoxic conditions. 29 MeHg accumulation in the water column is tentatively attributed primarily to the methylation of water column f.Hg( ii ) by methylating organisms on sinking particles as they decompose, 11,62 a phenomenon enhanced by the DOM of aromatic quality 38 that is more prevalent in Brownlee Reservoir during high flow years. The processes described above occur between February through early July in this river-reservoir system, when warm inflowing water enters the epilimnion of the reservoir.…”
Section: Resultsmentioning
confidence: 99%
“…UV-vis absorption spectra were measured from 190–800 nm and decadic absorbance values were converted to absorption coefficients aswhere α λ is the decadic absorption coefficient (cm −1 ), A λ is the absorbance, and l is the path length (cm). 47 The DOM specific ultraviolet absorbance at 254 nm (SUVA 254 ), a proxy for DOM aromaticity 47 that indicates DOM source and reactivity to Hg( ii ), 11,15,39 was calculated by dividing the α 254 (m −1 ) by DOC concentration (mg L −1 ). Spectral slopes were determined at wavelengths 275 to 295 nm ( S 275–295 ) and 350 to 400 nm ( S 350–400 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation